EFL gifted high school students' perceptions about making oral presentations in speaking classes : - Thái, Dương Hoàng Oanh (Cantho University, 2019)
This study is aimed to investigate students’ perceptions about making oral presentations in speaking classes and find out the difficulties students encounter while making oral presentations.